Eksperimen Dan Analisis Lebar Retak Pada Balok Beton Bertulang Pasca Paparan Suhu Tinggi - Rizki Prasetiya; Edhi Wahyuni; Wisnumurti Wisnumurti (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Cracking is one of the structural behaviors reviewed under the service boundary conditions. Cracks will be the gaps in the various substances in the reinforced concrete structures that will make the structure vulnerable. The fragility of building structures due to exposure to high temperatures or fires can be observed from the behavior of structures when the boundary conditions and maximum crack widths become one of the conditions to how the strength of the structure can survive. This research aims to find how big influence of high temperature on reinforced concrete beam especially to crack width. The test performed is a bending test with a beam-sized test object (10 x 15 x 120) cm. The variation of this research is normal reinforced concrete beam (BN), exposed to temperature 400°C (BS1), exposure temperature 600°C (BS2), and exposure temperature of 800°C. The results show that the decrease of bending strength from normal temperature to 400°C is 10%, from normal temperature to 600°C at 22% and from normal temperature to 800°C at 29%. For the average crack width at normal beam load load of 0,148 mm, then for 400°C beam decrease and the average crack width is 0,095 mm. For the average crack width when the load of beam service 600°C increased and gained 0,696 mm, for beam of 800°C crack width at service load 0,276 decreased compared to beam 600°C.